Persepsi tentang Seks Pranikah pada Remaja Putri yang Bertempat Tinggal di Kos dan di Rumah di Kasihan, Bantul - Umi Nur Isnaini; Dewi Astiti; Dyah Pradnya Paramita (Alma Ata University Press, 2014)
Premarital sex now already spread among adolescent, it makes adolescent not taboo anymore with sex. The results of recording by office of religious in Kasihan showed an increase in marriage among an early age, from 15 adolescent couples in January to October, 16 adolescent couples in November and 33 adolescent couples in December. The perception of premarital sex in adolescent should be known to raise awareness and to increase the high number of premarital sex in Yogyakarta. This study was aimed to know the perception of premarital sex in adolescent girls who live in rent room and home at Kasihan, Bantul. This study was used qualitative methode. Speakers were adolescent girls who lived in rent room and home at Kasihan, Bantul who had done premarital sex and who did not. Samples was obtained by purposive sampling with the triangulation. An instrument was used an interview guide of premarital sex perception, recorder sound and stationery. The results showed that adolescent only know about some of the definition premarital sex, it was also only know a part of impact because premarital sex and factors that encourage premarital sex. Factors that the most encourages adolescent premarital sex was because they had boyfriend. Attitudes of adolescent girls who did not hold premarital sex refuse and avoid premarital sex, while adolescent who had been doing premarital sex refuse premarital sex but still did it. The results of this study showed that there was no different perceptions about sex premarital in adolescent girls who live in rent room and home, but there was a differences perception of premarital sex and attitude of adolescent who had been doing premarital sex and who not doing premarital sex.